Interactions Between Antenatal Sulfadoxine-Pyrimethamine, Drug-Resistant Plasmodium falciparum Parasites, and Delivery Outcomes in Malawi. (28th March 2020) - Taylor, Steve M; Levitt, Brandt; Freedman, Betsy; Madanitsa, Mwayiwawo; Thwai, Kyaw-Lay; Kalilani-Phiri, Linda; Khairallah, Carole; Mwapasa, Victor; ter Kuile, Feiko O; Meshnick, Steven R
Abstract: Background: Sulfadoxine-pyrimethamine (SP) is used as intermittent preventive therapy in pregnancy (IPTp) for malaria in sub-Saharan Africa. The resistance marker dhps A581G has been associated with reduced IPTp-SP efficacy and enhanced morbidity in SP recipients. Methods: We measured SP-resistance allele frequencies in Malawian women participating in a trial comparing IPTp with SP against intermittent screening by rapid diagnostic tests (ISTp). We genotyped polymerase chain reaction-detected parasites using deep sequencing of SP-resistance alleles. Results: Among 125 placental infections, A581G-bearing parasites were associated with reduced birth weight (mean difference [MD], 252 g; 95% confidence interval [CI], 46–457; P = .017). Relative to ISTp, IPTp-SP was associated with higher birth weights in women with wild-type parasites (MD, 116 g; 95% CI, −40 to 272; P = .142) and lower birth weights in women with A581G-bearing parasites (MD, 192 g; 95% CI, −264 to 648; P = .385) ( P interaction = .033). Similar associations were noted on gestational age ( P interaction = .075). Amongst only IPTp-SP recipients, relative to women who last received SP > 4 weeks before delivery, recent SP receipt was associated with lower birth weight in women with wild-type parasites (MD, 118 g; 95% CI, −376 to 139; P = .361) and higher birth weight in women with A581G-bearing parasites (MD, 783 g; 95% CI, −20 to 1586; P = .054) ( P interaction = .005). Conclusions: The effectiveness in birth weight of IPTp-SP is compromised by A581G-bearing parasites, but there was no evidence that the adverse effects of these parasites are exacerbated by antenatal SP. ISRCTN Registry: www.isrctn.com/ISRCTN69800930 . Abstract : In Malawian pregnant women with placental malaria, the presence of parasites with the SP-resistance allele dhps A581G was associated with lower birth weights, but antenatal SP receipt did not exacerbate the adverse consequences of malaria in pregnancy.